Analisis Kinerja Thin Solar Panel 100 WP Untuk Meningkatkan Daya Keluaran - Achmad Raiski Maulana (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
The study “Analysis of the Performance of a 100 WP Thin Solar Panel to Increase Power Output” aims to determine how to improve the efficiency of thin solar panels and identify the causes of low power output in thin solar panels. The analysis methods employed include measuring electrical productivity under standard testing conditions, electrical power performance, electrical output power, and voltage-current (V-I) measurement results, which will be plotted as graphs. Data collection was conducted by measuring voltage, current, and power generated by Thin Solar Panels and Polycrystalline panels in the performance analysis of 100 WP Solar Panels. Additionally, this study also considers factors affecting the performance of Thin Solar Panels, such as sunlight intensity and surface temperature. The study was conducted using acrylic thicknesses of 1.5 mm, 2 mm, and 3 mm under both artificial light and sunlight, with two repetitions. The results of the study indicate that lower surface temperatures on Thin Solar Panels and Polycrystalline panels result in better power output. This study provides an important contribution to understanding and improving power output through the performance analysis of 100 WP Thin Solar Panels.